Inclusive education: technology of successful adaptation of students of «Group at risk» (Journal of Educational Sciences, 2018)
In the paper is studying the experience of students’ adaptation with special needs at the Faculty ofPhilosophy and Political Science of al-Farabi KazNU in pedagogical specialties. The generalization ofthe experience of educational and upbringing work affects the time interval from 2012 academic yearto the present. Directly in the specialties of «Pedagogy and Psychology», «Social Pedagogy and Selfknowledge», more than 300 young specialists were graduated, 4 of them with special needs. Graduateswith special needs not only completed a full course in specialties, but also now successfully realizethemselves in the society, helping to develop not only to themselves, but to adapt to other pupils whoneed pedagogical support. As a result of the generalization of experience, a comprehensive conceptwas developed, how to accompany and facilitate the successful adaptation of students with disabilitiesin higher school. This concept, through an integrated and systematic approach, includes tools and integratedtechnologies for the successful adaptation of students at the «risk group»: an inclusive office, technology «Social Modeling», technology «Tutor», technology «Roadmap» («Meeting» form), «TeacherSupport» «,» Walking «technology,» Team collaboration «technology,» Consultation «technology, MobileSchool technology. In this model, we tested the role of assistant «Tutor» and assistant (volunteer) fromfellow classmates. The concept integrates the results of an analysis of the survey of specialists from inclusiveeducational organizations in Almaty and the positive results of the university’s practice.Key words: inclusions, students with special needs, support technologies, coach technologies.